Legitimizacija imaginarnog i subverzija povijesnog u romanesknom diskursu Dževada Karahasana, Milorada Pavića i Jasne Horvat - Kos-Lajtman, Andrijana (Slavia Centralis, 2020)
Through the analysis of the key novels by three authors from various national and cultural mentalities − a Bosnian and Herzegovinian writer Dževad Karahasan (Vzhodni divan, 1989), a Serbian writer Milorad Pavić (Hazarski slovar, 1984) and a Croatian writer Jasna Horvat (Az, 2009) – thematic and worldview similarities expressed in their novelistic discourses are discussed. All three authorial practices are characterized by close worldview axes, which are primarily demonstrated in the affirmative attitude towards the phantasmagorical and the imaginary on the one hand and the relativizing attitude towards the historical (and historiographical) on the other hand.